Dose-related effects of extracorporeal shock waves on orthodontic tooth movement in rabbits - Onur Demir (Nature Portfolio, 2021)
Abstract The purpose of this animal study is to investigate the quantitative effects of extracorporeal shock waves applied at two different impulses and with two different applicators on orthodontic tooth movement. Thirty-five New Zealand rabbits were randomly divided into five groups (n = 7): the four experimental extracorporeal shock wave groups—focused/500 impulses, focused/1000 impulses, unfocused/500 impulses, and unfocused/1000 impulses—and the control group. Orthodontic tooth movement was achieved by application of reciprocal force between two maxillary incisors. In the experimental groups, animals received 500 or 1000 impulses of extracorporeal shock waves at 0.19 mJ/mm2 with focused or unfocused applicators depending on the group to which they belonged. These experiments were conducted on days 0, 7, and 14. Orthodontic tooth movement was measured with 0.01 mm accuracy at one-week intervals. On days 7 and 21, the bone-specific alkaline phosphatase levels were measured from blood samples. After 21 days, the animals were sacrificed and the area between the two maxillary incisors was stereologically examined. Orthodontic tooth movement in the focused/500 impulses and focused/1000 impulses groups was significantly increased compared to the control group. A significant difference in bone-specific alkaline phosphatase levels between the unfocused/500 impulses and control groups was found at 21st day. Stereological analysis showed that there were significant increases of the formation of new bone, connective tissue, and vessels in the experimental groups. The application of extracorporeal shock waves, especially with a focused applicator, could accelerate orthodontic tooth movement.